Potential of Aqueous Leaves Extract of Jatropha Gossypiifolia Seed Against Highly Active Antiretroviral Therapy Induced Hepatotoxicity in Rats - Umaru, Isaac John; Akafa, Tensaba Andes; Akem, Ingwu Joseph; Oteng, Joseph; Ngbede, Ocheifa Mathew; Utioukpan, Ashaka Fidelis; Mijinyawa, Aboki Nwunuji; Akam, Odok Endurance; Ekup, Ogholo Ogholo (African Journal of Clinical Medicine and Pharmacy Research, 2025)
While many methods exist for measuring the impact of AIDS, treatment remedy the human development approach focuses on people rather than medical or economic indicators. Human Development Index captures three basic dimensions of human development: a long and healthy life—measured by life expectancy at birth; knowledge—measured by adult literacy and school enrolment; and standard of living—measured by per capita gross domestic product. Thus, investigate the hepatoprotective activity of aqueous extract of Jatropha gossypiifolia seed in highly active antiretroviral therapy administered rats. Liver is a metabolically active organ responsible for many vital life functions. It performs many activities that are critical for survival. Due to its important activities, the liver is exposed to a number of insults and is one of the body's organs most subject to injury. In spite of tremendous advances in modern medicine, there are hardly any reliable drugs that protect the liver from damage and/or help in regeneration of hepatic cell. It is, therefore, necessary to search for effective and safe herbal drugs for the treatment of liver disease to replace currently used drugs of doubtful efficacy and safety. Hence, the need to evaluate the aqueous extract of Jatropha gossypiifolia seed in highly active antiretroviral therapy (Lamivudine, Zidovudine and Efavirenz) administered rats. Sixty rats weighed between 150-200g were randomly divided into six groups and each group comprised of ten rats. Rats in group I were administered with distilled water. Rats in group II were administered with highly active antiretroviral therapy only. Rats in groups III - VI were administered 100, 200, 400 and 600 mg/kg Jatropha gossypiifolia seed plus highly active antiretroviral therapy respectively. The treatments were given orally for 28 consecutive days. On the 29th day, all rats were sacrificed under light diethyl ether anaesthesia; blood samples were collected for the assessment of biochemical parameters, while Serum levels of liver enzymes ALT, AST, ALP, and GGT were significantly (p<0.05) increased and albumin concentration was significantly decreased in animals treated with highly active antiretroviral therapy as compared to the normal control. Treatment of highly active antiretroviral therapy exposed animals with Jatropha gossypiifolia seed showed marked improvement in biochemical findings. Rise in liver enzymes was almost restored to normal in animals treated with Jatropha gossypiifolia seed. Jatropha gossypiifolia seed through its antioxidant activity effectively protects highly active antiretroviral therapy induced liver toxicity.